2009
DOI: 10.1073/pnas.0810987106
|View full text |Cite
|
Sign up to set email alerts
|

Live cell microscopy analysis of radiation-induced DNA double-strand break motion

Abstract: We studied the spatiotemporal organization of DNA damage processing by live cell microscopy analysis in human cells. In unirradiated U2OS osteosarcoma and HeLa cancer cells, a fast confined and Brownian-like motion of DNA repair protein foci was observed, which was not altered by radiation. By analyzing the motional activity of GFP-53BP1 foci in live cells up to 12-h after irradiation, we detected an additional slower mobility of damaged chromatin sites showing a mean square displacement of Ϸ0.6 m 2 /h after e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
107
2

Year Published

2011
2011
2019
2019

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 163 publications
(121 citation statements)
references
References 45 publications
12
107
2
Order By: Relevance
“…Using soft X-rays generating tracks of DSB, Nelms and colleagues (Nelms et al, 1998) showed positional stability of DNA lesions. Similar conclusions were drawn from time-lapse measurements of 53BP1 repair foci (Kruhlak et al, 2006;Jakob et al, 2009) and from recordings of the position of broken DNA ends (Soutoglou et al, 2007). The decrease in …”
Section: Resultssupporting
confidence: 63%
“…Using soft X-rays generating tracks of DSB, Nelms and colleagues (Nelms et al, 1998) showed positional stability of DNA lesions. Similar conclusions were drawn from time-lapse measurements of 53BP1 repair foci (Kruhlak et al, 2006;Jakob et al, 2009) and from recordings of the position of broken DNA ends (Soutoglou et al, 2007). The decrease in …”
Section: Resultssupporting
confidence: 63%
“…Although the decreasing foci numbers in the middle region roughly follow the theoretical prediction, the plateaus in the smaller and larger categories reflect expected experimental restrictions. The resolution of the focus structure with a typical size of roughly 0.5 μm and slight foci movement processes (37,38) (Fig. S2E) might contribute to the deviation from the 1/r 2 dependency below 0.4 μm, and also might give rise to a slightly steeper decrease than expected above 0.4 μm.…”
Section: Resultsmentioning
confidence: 99%
“…In this case, enhanced mobility requires 53BP1 and the INM proteins SUN1 and SUN2 (Dimitrova et al 2008;Lottersberger et al 2015). On the other hand, other studies have observed that chromatin containing DSBs exhibits limited mobility (Kruhlak et al 2006;Soutoglou et al 2007;Jakob et al 2009). This apparent discrepancy may be attributed to the type of damage incurred and/or to the way it activates the ATM/ATR checkpoint, which was shown in yeast to contribute to DSB motion (Seeber et al 2013).…”
Section: Increasing Mobility: a Functional Requirement For Homology Smentioning
confidence: 96%